The measles epidemic in northern Kosovo and Metohija, Serbia, October 2017−August 2019 - Aritonovic Pribakovic, Jelena; Katanic, Natasa; Ilic, Aleksandra; Stojanovic Tasic, Mirjana; Mitic, Nebojsa R; Mirkovic, Momcilo; Radomirovic, Danica; Milentijevic, Milica; Mirkovic, Milos; Katanic, Radoslav (The Journal of Infection in Developing Countries, 2022)
Introduction: Measles is among the most contagious and vaccine-preventable respiratory diseases. The aim of this research was to describe the socio-demographic profile, clinical manifestations and laboratory parameters of measles patients hospitalized at Kosovska Mitrovica Clinical Centre during the 2017−2019 outbreak. Methodology: The prospective study included all patients that had contracted measles (107) who were hospitalized at Kosovska Mitrovica Clinical Centre during the outbreak. All complications that led to hospitalization were analyzed and the frequencies of complications with respect to patient age and vaccination status were recorded. Results: More than half (51%) of the patients were unvaccinated. Patients’ age varied statistically significantly with respect to vaccination status. Pneumonia was noted in 65% of the patients from the younger age group, compared to 32% of adults, and this difference was statistically significant. Hepatitis was a significantly more frequent complication in adults, affecting 36% of measles patients in this age group, compared to only 7% of those aged below 18 years. In the unvaccinated group, 71% pneumonia frequency was noted, compared to 11% and 35% in the vaccinated and unknown vaccination status groups, respectively. The differences in frequencies based on vaccination status were statistically significant. Conclusions: Most hospitalized patients were unvaccinated. Complications showed a significant difference with respect to the age and vaccination status of patients. Therefore, it is necessary to carry out continuous health promotion activities to raise awareness among the entire population of the importance and need for vaccination of children against measles, but also adults who have not been previously vaccinated.